Polish new-critical philosophy vs. the philosophy of Kant - Szotek, Barbara (Folia Philosophica, 2004)
The author of the article attempts at presenting the output of transcendental philosophy of Kant at the turn of the 19th century in Poland through the creative output of Adam Mahrburg and Marian Massonius. These thinkers were the most outstanding representatives of the Polish new-critical philosophy, which was numbered among the second [critical] stage of positivism in Poland that had raised the importance of cognizance in philosophy. It resulted in Kant’s provenience of philosophical criticism. However, their attitude towards the philosophy of Kant was ambivalent, and this is what the author tries to show by examining the stance of Massonius in this case.